スライドグラス マイセツ ホウ ニ ヨリ ナンキョク ドジョウ カラ ケンシュツ サレタ ソウルイ - 大谷, 修司; オオタニ, シュウジ; 秋山, 優; アキヤマ, マサル; 神田, 啓史; カンダ, ヒロシ; Ohtani, Shuji; Akiyama, Masaru; Kanda, Hiroshi (1991)
P(論文) 南極ラングホブデ雪鳥沢において, スライドグラス埋設法を用い, 土壌含水量と関連させ, 土壌藻類の種類組成とその分布を調査した。沢の5ヵ所において, 沢の流れに直交する方向に数m間隔で3~6の地点, スライドグラスを垂直に1988年1月より翌年1月まで埋設した。種類としては, 11種類の藍藻類, 8種類の緑藻類, 4種類の珪藻類が検出された。それらのうち, Actinotaenium cucurbitaとPinnularia borealisがしばしば優占種として出現した。走査型電子顕微鏡による観察では, 珪藻類は薄い粘液を分泌し, 糸状性藍藻類のLyngbya martensianaは厚い粘液を分泌してスライドグラスに固着していた。藻類の種類数, 細胞数及び土壌中のクロロフィル量は土壌の含水量と強い関連が見られた。これらはいずれも土壌含水量が高い沢近くの地点では多く, 沢から数m離れると土壌含水量は激減し, そこでは著しく少なくなった。 The species composition and distribution of soil algae in situ were investigated by the direct observation using the contact slide method with reference to the available water in soils of the Yukidori Valley, Langhovde, Antarctica. Glass slides were vertically buried at five sites with a few meters intervals along a stream for a year from January 1988. Eleven taxa of Cyanophyceae, eight taxa of Chlorophyceae and four taxa of Bacillariophyceae were recognized on the collected glass slides. Actinotaenium cucurbita (RALFS) TEILING and Pinnularia borealis EHRENB. were often dominant. The results of the observation by the scanning electron microscope showed that diatoms secreted thin mucilage, but a filamentous blue-green alga, Lyngbya martensiana MENEGH. secreted thick mucilage and adhered to the surface of glass slides. Both the species number and the algal cell number of the soil algae and the chlorophyll content in soils were well related to the water content of soils. Values of these three items were high at the nearest transect points to the stream where the water content of soils was high, and suddenly decreased at a few meters distance from the stream where the water content of soils was low. departmental bulletin paper